Silver nanowire networks with preparations and applications: a review - Tan, Dongchen; Jiang, Chengming; Li, Qikun; Bi, Sheng; Song, Jinhui (Journal of materials science. Materials in electronics, 2020)
Due to the comprehensive performance on optoelectronics and mechanics, flexible electronics based on silver nanowires (AgNWs) network have attracted many attentions and achieved diverse functions comparing traditional electronic device. As more researches have been progressing, major advanced devices using AgNWs have been made, such as flexible optoelectronic devices, electromagnetic shielding, bio-robot’s components, and intelligence sensors and influence in human daily life. Comparing to the traditional transparent conductive material, such as indium tin oxide (ITO), AgNWs network performs more excellent in optoelectronics, mechanical properties and stability, and gradually appears on transparent flexible applications. However, a series of problems would be encountered in the fabrication process, such as geometric controllability, electronic and mechanical stability, and device manufacture. Plenty of studies on AgNWs for these interacting aspects have been conducted and achieved excellent progress. With these considerations, the latest progress to AgNWs network preparation and applications are reviewed in terms of manufacturing process, performance evaluation and enhancement, typical applications in this paper. The main challenges and prospects of the AgNWs network in future applications are briefly evaluated.